RENDAHNYA HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI SEKOLAH MENENGAH ATAS - Elisa Elisa; Sulistyarini Sulistyarini; Husni Syahrudin (Universitas Tanjungpura, 2018)
AbstractThis study aims to describe what factors can affect the low learning outcomes of students who viewed from external and internal factors in class XII IIS 2 SMAN 02 Pontianak. This research is descriptive research. This research is located at SMAN 02 Pontianak, Jalan R.E Martadinata Pontianak in class XII IIS academic year 2017/2018. Data pengumpula using the method of konsioner and interview. Data analysis using Data Reduction technique, display data, cloncusion and drawing / veriviction. The results showed as follows. (1) Internal factors that affect the low of student learning outcomes in class XII IIS 2 SMAN 02 Pontianak (rest period: 65,79%; intelegence: 86,84%; attitude: 81,58%; talent: 81,58%; : 84.21%, motivation: 84.21%). (2) External factors affecting low student learning outcomes in class XII IIS 2 SMAN 02 Pontianak (community environment: 31.58%; family environment: 34.21%; school facilities: 100%; residential facility: 26.32 %; stationery: 52.63%, convenience at school: 100%).Keywords: Low Learning Outcomes, Internal Factors, External Factors